Vitamin D, Folate, and Cobalamin Serum Concentrations Are Related to Brain Volume and White Matter Integrity in Urban Adults - Beydoun, May A.; Shaked, Danielle; Hossain, Sharmin; Beydoun, Hind A.; Katzel, Leslie I.; Davatzikos, Christos; Gullapalli, Rao P.; Seliger, Stephen L.; Erus, Guray; Evans, Michele K.; Zonderman, Alan B.; Waldstein, Shari R. (Frontiers in Aging Neuroscience, 2020)
Background and objectives: Lower vitamin status were linked to cognitive deficits, pending mechanistic elucidation. Serum 25-hydroxyvitamin D [25(OH)D], folate and cobalamin were explored against brain volumes and white matter integrity (WMI). Methods: Three prospective waves from Healthy Aging in Neighborhoods of Diversity Across the Life Span (HANDLS) study were used [Baltimore, City, MD, 2004-2015, N=183-240 urban adults (Agev1: 30-64y)]. Serum vitamin 25-hydroxyvitamin D [25(OH)D], folate and cobalamin concentrations were measured at visits 1 (v1:2004-2009) and 2 (v2:2009-2013), while structural and diffusion Magnetic Resonance Imaging (sMRI/dMRI) outcomes were measured at vscan:2011-2015. Top 10 ranked adjusted associations were corrected for multiple testing using familywise Bonferroni (FWER<0.05) and false discovery rates (FDR, q-value<0.10). Results: We found statistically significant (FWER<0.05; β±SE) direct associations of 25(OH)D(v1) with WM volumes [overall: +910±336 /males: +2054±599], occipital WM; [overall: +140±40, males: +261±67 and Agev1>50y: +205±54] ; parietal WM; [overall: +251±77, males: +486±129 and Agev1>50y: +393±108] and left occipital pole volume [overall: +15.70±3.83 and above poverty: 19.0±4.3], findings replicated for 25(OH)D (v2-v1) annualized exposure, which was also linked with greater WMI (fractional anisotropy, FA) in the anterior limb of the internal capsule or ALIC; FWER<0.05 [Overall: +0.0020±0.0004; Whites: +0.0024±0.0004] and in the cingulum (hippocampus) [Overall: +0.0016±0.0004]. Only trends were detected for cobalamin exposures (q<0.10), while serum folate (v1) was associated with lower mean diffusivity (MD) in ALIC, reflecting greater WMI, overall. Conclusions: Among urban adults, serum 25(OH)D status and increase were consistently linked to larger occipital and parietal WM volumes and greater region-specific WMI. Pending longitudinal replication of our findings, randomized controlled trials of vitamin D supplementation should be conducted against brain marker outcomes.